Effect of Maternal Body Mass Index on Neonatal Outcomes among Pregnant Women: A Prospective Cohort Study - Pandya, Ms. Kaveriben; Gohil, Dr. Jagdish T (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Maternal nutritional status during pregnancy plays a crucial role in determining neonatal health outcomes. Body Mass Index (BMI) is a widely used indicator of maternal nutritional status and has been associated with various adverse neonatal outcomes. Understanding the relationship between maternal BMI and neonatal outcomes is essential for identifying high-risk pregnancies and improving perinatal care. Objective: To assess the effect of maternal Body Mass Index on neonatal outcomes among pregnant women attending selected hospitals in Dadra and Nagar Haveli. Methods: A quantitative prospective cohort study was conducted among 200 antenatal mothers recruited during early pregnancy from selected hospitals in Dadra and Nagar Haveli. Maternal BMI was calculated using measured height and weight and categorized according to the World Health Organization classification as underweight, normal weight, overweight, and obese. Participants were followed until delivery, and neonatal outcomes including birth weight, gestational age at birth, APGAR score at 5 minutes, and neonatal intensive care unit (NICU) admission were assessed. Data were analysed using descriptive statistics, Chi-square test, one-way ANOVA, and multivariable logistic regression. Statistical significance was considered at p < 0.05. Results: The mean maternal BMI was 24.18 ± 4.71 kg/m². Of the participants, 13.0% were underweight, 49.0% had normal BMI, 24.5% were overweight, and 13.5% were obese. Significant associations were observed between maternal BMI and neonatal birth weight (χ² = 24.76, p < 0.001), gestational age at birth (F = 4.91, p = 0.003), APGAR score at 5 minutes (F = 9.84, p < 0.001), and NICU admission (χ² = 13.41, p = 0.004). Logistic regression analysis identified underweight BMI (AOR = 2.84, p = 0.006) and obese BMI (AOR = 3.21, p = 0.003) as significant predictors of adverse neonatal outcomes. Conclusion: Maternal BMI significantly influences neonatal outcomes. Both underweight and obese mothers were at increased risk of adverse neonatal outcomes, highlighting the importance of routine BMI assessment, nutritional counselling, and targeted antenatal interventions to optimize neonatal health.